2019
DOI: 10.1111/cmi.13085
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal phosphatidylinositol‐specific phospholipase C potentiates lung injury via complement sensitisation

Abstract: Staphylococcus aureus is frequently isolated from patients with community-acquired pneumonia and acute respiratory distress syndrome (ARDS). ARDS is associated with staphylococcal phosphatidylinositol-specific phospholipase C (PI-PLC); however, the role of PI-PLC in the pathogenesis and progression of ARDS remains unknown. Here, we showed that recombinant staphylococcal PI-PLC possesses enzyme activity that causes shedding of glycosylphosphatidylinositol-anchored CD55 and CD59 from human umbilical vein endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In addition to the Δ plc strain, the complemented strain was generated by reintroducing the plc gene into the Δ plc strain (designated as Δ plc :: plc ). Since a previous study demonstrated the necessity of His-80 in the activity of S. aureus PI-PLC 25 , another strain was constructed for the complemented strain with mutated plc gene that encoded His-80-mutated catalytically inactive mutants of PI-PLC (designated as Δ plc :: plc-MT ). This would help determine the role of PI-PLC activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the Δ plc strain, the complemented strain was generated by reintroducing the plc gene into the Δ plc strain (designated as Δ plc :: plc ). Since a previous study demonstrated the necessity of His-80 in the activity of S. aureus PI-PLC 25 , another strain was constructed for the complemented strain with mutated plc gene that encoded His-80-mutated catalytically inactive mutants of PI-PLC (designated as Δ plc :: plc-MT ). This would help determine the role of PI-PLC activity.…”
Section: Resultsmentioning
confidence: 99%
“…The GPI-anchored proteins CD55 and CD59 present on keratinocytes are suggested to play a role in the alleviation of AD 39 . Since S. aureus PI-PLC was observed to cleave CD55 and CD59 from the surface of human umbilical vein endothelial cells and mouse pneumocytes 25 , the PI-PLC-mediated shedding of CD55 and CD59 from keratinocytes might enhance epidermal penetration by S. aureus, epidermal hyperplasia, and immune cell infiltration in S. aureus-infected skin in AD model mice. www.nature.com/scientificreports/ www.nature.com/scientificreports/ Although keratinocyte-derived AMPs kill extracellular S. aureus in the epidermis and inhibit epidermal penetration by S. aureus, AMPs are less effective in combating intracellular S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complement depletion in mice with cobra venom factor CVF) was performed as describe previously [25]. Briefly, CVF (Quidel) was diluted in PBS at a concentration of 2.5 U/100 μl.…”
Section: In Vivo Complement Depletion With Cobra Venom Factor (Cvf)mentioning
confidence: 99%